LongForm or Microcontent? An analysis of supports for digital content courseware - Santana Gomes, Nicole; Ximenes Martins, Ronei; Azevedo, Daniela (RED : revista de educación a distancia, 2021)
Este artículo compara el formato de Microcontenido (MC), de unidades de información, pequeñas y fragmentadas, con el formato LongForm (LF) con contenido profundo y extenso, como soporte para materiales didácticos para cursos presenciales o no. El objetivo es encontrar alternativas que no simplifiquen el contenido o generen daños al proceso educativo. Se aplicó una actividad en ambos formatos a 67 estudiantes de una Universidad de Minas Gerais, que reveló las preferencias de los participantes: el MC demostró ser bueno para la construcción de materiales didácticos de menor tamaño y baja densidad de contenido. El formato LF es apropiado para contenido complejo. Éste se presenta como una alternativa viable para cursos en línea ya que está constituido por un único espacio virtual donde se pueden introducir textos más grandes y diversos recursos multimedia para facilitar la comprensión y enriquecer el contenido. Por otro lado, el formato MC está indicado para situaciones que ofrecen materiales didácticos en línea para hacer revisiones, presentación inicial y temas poco densos en extensión y en profundidad conceptual. The article compares the Microcontent format (MC), with their small and fragmented information units, and LongForm format (LF) with in-depth and extensive content; when use as digital content for distance or face-to-face education. The research seeks alternatives that do not simplify the contents, nor they harm the educational process. An educational activity, elaborated in both formats, was applied to 67 students from a university of Minas Gerais state, in Brazil. Observation of student activity revealed their preferences: MC has been shown to be good for building learning with smaller materials in both size and content density, but LF has been appropriate when dealing with complex, dense, multimedia-requiring contents to facilitate understanding. It was confirmed that the LF presents itself as a viable alternative for online studying because it is constituted by a single virtual space where larger texts and varied multimedia resources can be inserted to enrich the educational material and to offer the full content for students. On the other hand, the use of the MC is indicated to offer online learning materials intended for revision, the initial presentation and for materials use in minor subjects, both in extension and conceptual deepening.